The relationship between leg muscle strength and static balance in surfers - Cokorda Istri Ajeng Prameswari; I Dewa Gede Alit Kamayoga; I Gusti Ayu Artini; I Made Niko Winaya (Physical Therapy Journal of Indonesia, 2024)
Background: Surfing is a type of water sport that involves playing on the waves by using a surfboard to maneuver on the waves. It requires good static balance and good leg muscle strength. Methods: The method used in the analytical cross-sectional study design. This research was conducted on February 25, 2023. The inclusion criteria for male surfers aged 18-25 years have ever surfed (nor in the training or learning process). According to the screening assessment, the exclusion criteria included individuals who have experienced a lower extremity injury in the last 3 months (except lacerations or injuries with open wounds). The sampling technique used was a nonprobability sampling method with a purposive sampling technique. The number of samples obtained in this research was 46 samples. Results: Data collection was carried out by measuring leg muscle strength and static balance. Leg muscle strength was measured with a leg dynamometer while static balance was measured with the Stork Standing Test. Based on the non-parametric Spearman rho analysis test, the value of p = 0.000 (p < 0.05) and the correlation coefficient r = 0.954. Conclusion: Based on the research results, it can be concluded that there was a significant relationship between leg muscle strength and static balance in surfers.